Numerical simulation of vertical water impact of asymmetric wedges by using a finite volume method combined with a volume-of-fluid technique. (15th July 2018) - Bilandi, Rasul Niazmand; Jamei, Saeed; Roshan, Fatemeh; Azizi, Mohammad
Abstract: In the present paper, two dimensional (2-D) symmetrical and asymmetrical wedges entering calm water vertically at constant speed are simulated based on the finite volume method (FVM). In order to obtain pressure distribution and free surface profile, volume of fluid (VOF) method coupled with FVM are utilized in Star CCM+. Pressure distribution and free surface elevation are presented for each different symmetry and asymmetry deadrise angles. Low pressure area of the flow due to asymmetric impact or vertical impact velocity is shown in relation to the present study. Comparison of the obtained results against previously published works shows good agreement. Highlights: Effect of dead rise angles and heel angles. The pressure distribution and free surface elevation. Low pressure area.